Hospedaje y trabajo femenino en Pamplona a finales del siglo XVIII - Erdozáin Azpilicueta, Pilar; Mikelarena Peña, Fernando (Huarte de San Juan. Geografía e Historia, 1998)
This article studies the participation of women in urban labour markets, and in particular the activity of lodging carried out by women in Pamplona at the end of the 18th century. The practice of lodging allowed women to get an additional income -derived from the lodgers, accommodation, food and laundry- without leaving home, thus permitting them to combine the house-hold chores with those related to guest accommodation.
Keywords: Lodging; femine labour; underground market; urban family economies